Does Grade Level Matter for the Assessment of Business Process Management Maturity? - Renata Gabryelczyk (Naše gospodarstvo/Our economy, 2016)
The purpose of this paper is to create and test the practical application of a business process management maturity assessment conducted at two different grade levels (management and professional level) in an organization. The conceptual framework for this research includes creating a business process maturity indicator (BPMI) for six process areas: strategy, documentation, optimization, implementation, execution, and controlling. The comparative analysis of the business process management maturity is performed using the BPMI on two cases: inside a single organization and the sector internally.